Impairment losses: causes and impacts - Fernandes, Joaquim Santana; Gonçalves, Cristina; Guerreiro, Cristina; Pereira, Luis Nobre (Review of Business Management, 2016)
Purpose – To analyze recognition of impairment losses in tangible and intangible assets, and their relevance to investors in companies listed in the Lisbon and Madrid Stock Exchange (2007-2011). Methodology – Quantitative analysis of a panel data sample of 80 companies listed in the Lisbon and Madrid Stock Exchange (2007-2011) was carried out. Panel data linear and non-linear regression models were estimated. Findings – We found that the amount of impairment losses showed an upward trend, and that these losses are most significant among intangibles, especially goodwill (GW). We also found that the probability of recognition of impairment losses is positively influenced by the dimension of entities and negatively by market value (p < 0.10). Portuguese export-oriented companies have a higher probability of not recognizing impairments. However, Portuguese companies with higher market values have greater probability of recognizing impairment losses, contrary to the sample as a whole, in which the relationship is negative (p < 0.10). The results also suggest that there is a smoothing effect on results because of impairments, especially in IBEX35 companies. As to the relevance of impairment losses to market value, we confirm a significant negative relationship, in line with conclusions from previous studies. Originality/value – This study contributes to the introduction of the cultural factor in this analysis, highlighting the differentiated behaviors between Portuguese and Spanish companies.